Filozofia pierwsza, metafizyka, ontologia. Z dziejów pojęć, koncepcji i doktryn - Rosiak, Marek (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2001)
The aim of the paper is to provide information on the evolution of three correlated notions listed above. Only constructive standpoints, assuming possibility of the relevant sciences are taken into account, no criticism of metaphysics as such, etc. is mentioned. Included are some opinions on the methodology of these disciplines. As Polish reader still cannot find information concerning many basic issues in this field of study, some elements of doxography are also included to fill the most nagging gaps. This provisional survey is intended to serve as a complementary source of information in the field of ontology for students of philosophy.